1 Digest of the Laws of the State of Florida, From the Year One Thousand Eight Hundred and Twenty-Two, to the Eleventh Day of March, One Thousand Eight Hundred Eighty-One Inclusive 403 (James F. McClellan ed., 1881). - (:unkn) unknown (My University, 1881)
§ 13: Prohibited the concealed carry of any kind of arms whatsoever, or carry any dirk, pistol, or other arm or weapon. Violators fined not exceeding one hundred dollars or imprisonment not exceeding six months.
Keywords: CARRY; CARRY - CONCEALED